2023
DOI: 10.3847/1538-4357/aca667
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decay of a Penumbral Sector Associated with a Strong Light Bridge in Active Region NOAA 12680

Abstract: We present observations of the rapid decay of a penumbral sector associated with a strong light bridge (LB) in the active region NOAA 12680 by analyzing the scattered light-corrected Solar Dynamics Observatory/Helioseismic and Magnetic Imager data. At the beginning of penumbral decay, some dark structures gradually broke away from the umbra to which they were attached. The intensity, vertical field strength, and magnetic inclination of the dark structures are intermediate between those of the umbra and penumbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Second, the umbral and penumbral regions satisfy the following criteria, I umbra 0.5I 0 and 0.5I 0 < I penumbra 0.9I 0 , where I umbra and I penumbra are the continuum intensities of the umbra and penumbra, respectively. Many studies show that the inner boundary threshold of the penumbra lies in 0.5I 0 -0.6I 0 (Benko et al 2018;Jurčák et al 2018;Schmassmann et al 2018;Löptien et al 2020;García-Rivas et al 2021;Li et al 2023), and the outer boundary threshold of the penumbra is around 0.9I 0 (Li et al 2021(Li et al , 2022(Li et al , 2023Murabito et al 2021). We determine the umbral boundaries for each image using the fixed threshold of 0.5I 0 , and the determined umbral boundaries are well adapted to the entire sunspot evolution during the observation.…”
Section: Observations and Data Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the umbral and penumbral regions satisfy the following criteria, I umbra 0.5I 0 and 0.5I 0 < I penumbra 0.9I 0 , where I umbra and I penumbra are the continuum intensities of the umbra and penumbra, respectively. Many studies show that the inner boundary threshold of the penumbra lies in 0.5I 0 -0.6I 0 (Benko et al 2018;Jurčák et al 2018;Schmassmann et al 2018;Löptien et al 2020;García-Rivas et al 2021;Li et al 2023), and the outer boundary threshold of the penumbra is around 0.9I 0 (Li et al 2021(Li et al , 2022(Li et al , 2023Murabito et al 2021). We determine the umbral boundaries for each image using the fixed threshold of 0.5I 0 , and the determined umbral boundaries are well adapted to the entire sunspot evolution during the observation.…”
Section: Observations and Data Reductionsmentioning
confidence: 99%
“…The fragmentation and disintegration of the sunspot magnetic flux are associated with light bridges (Vazquez 1973;Louis et al 2012;Murabito et al 2021) and moving magnetic features (MMFs) (Kubo et al 2008a). Li et al (2023) observed that the formation of a light bridge may accelerate the decay of the penumbra within a decaying sunspot. A number of researches have indicated that the magnetic field of the penumbra becomes more vertical during sunspot decay (Li et al 2021;Peng et al 2023).…”
Section: Introductionmentioning
confidence: 99%